Modeling the Contribution of Allosteric Regulation for Flux Control in the Central Carbon Metabolism of E. coli - Machado, Daniel; Herrgård, Markus J.; Rocha, Isabel (Frontiers in Bioengineering and Biotechnology, 2015)
Modeling metabolism is fundamental for cell factory design. Central carbon metabolism (CCM) is particularly important as it provides the energy and precursors for other biological processes. However, the complex regulation of CCM has not been fully unraveled. Recent studies have shown that CCM is mostly regulated at post-transcriptional levels. To better understand the role of allosteric regulation in controlling the metabolic phenotype, we expand a CCM model of E. coli with allosteric interactions. This model is used to integrate multi-omics datasets and analyze the coordinated changes in enzyme, metabolite and flux levels. We observe cases where allosteric interactions have a major contribution to the metabolic adjustments. Also, we develop a constraint-based method (arFBA) for simulation of metabolic flux distributions accounting for allosteric interactions. This method is used for systematic prediction of potential allosteric regulation under the given experimental conditions based on experimental flux data. The results reveal the importance of key regulatory metabolites, such as fructose-1,6-bisphosphate, in controlling the metabolic flux. Accounting for allosteric interactions in metabolic reconstructions reveals a hidden topology in metabolic networks, improving our understanding of cellular metabolism and fostering the development of novel simulation methods that account for this type of regulation.